2015
DOI: 10.3389/fncel.2015.00222
|View full text |Cite
|
Sign up to set email alerts
|

Homolog of protein kinase Mζ maintains context aversive memory and underlying long-term facilitation in terrestrial snail Helix

Abstract: It has been shown that a variety of long-term memories in different regions of the brain and in different species are quickly erased by local inhibition of protein kinase Mζ (PKMζ), a persistently active protein kinase. Using antibodies to mammalian PKMζ, we describe in the present study the localization of immunoreactive molecules in the nervous system of the terrestrial snail Helix lucorum. Presence of a homolog of PKMζ was confirmed with transcriptomics. We have demonstrated in behavioral experiments that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 36 publications
0
8
1
Order By: Relevance
“…We note that Volk et al had reported ZIP induces decreases in both tetanized and untetanized pathways in slices ( Volk et al, 2013 ). These results conflict with evidence from a large number of studies showing exclusive actions of ZIP in tetanized or facilitated pathways and not in baseline pathways, including seven studies in brain slices of fEPSPs ( Ling et al, 2002 ; Serrano et al, 2005 ; Sajikumar et al, 2005 ; Navakkode et al, 2010 ; Lin et al, 2012 ; Panaccione et al, 2013 ; Chen et al, 2015 ), four studies of EPSCs ( Li et al, 2010 ; Yao et al, 2013 ; Velez-Hernandez et al, 2013 ; Li et al, 2014 ), two studies in model systems ( Cai et al, 2011 ; Balaban et al, 2015 ), and four studies in vivo of fEPSPs ( Pastalkova et al, 2006 ; Madronal et al, 2010 ; Dong et al, 2015 ) and evoked responses ( Cooke and Bear, 2010 ), as well as evidence of stable basal properties of hippocampal neurons following ZIP injections recorded in vivo ( Barry et al, 2012 ). DOI: http://dx.doi.org/10.7554/eLife.14846.004
10.7554/eLife.14846.005 Figure 1—figure supplement 2.
…”
Section: Resultscontrasting
confidence: 88%
“…We note that Volk et al had reported ZIP induces decreases in both tetanized and untetanized pathways in slices ( Volk et al, 2013 ). These results conflict with evidence from a large number of studies showing exclusive actions of ZIP in tetanized or facilitated pathways and not in baseline pathways, including seven studies in brain slices of fEPSPs ( Ling et al, 2002 ; Serrano et al, 2005 ; Sajikumar et al, 2005 ; Navakkode et al, 2010 ; Lin et al, 2012 ; Panaccione et al, 2013 ; Chen et al, 2015 ), four studies of EPSCs ( Li et al, 2010 ; Yao et al, 2013 ; Velez-Hernandez et al, 2013 ; Li et al, 2014 ), two studies in model systems ( Cai et al, 2011 ; Balaban et al, 2015 ), and four studies in vivo of fEPSPs ( Pastalkova et al, 2006 ; Madronal et al, 2010 ; Dong et al, 2015 ) and evoked responses ( Cooke and Bear, 2010 ), as well as evidence of stable basal properties of hippocampal neurons following ZIP injections recorded in vivo ( Barry et al, 2012 ). DOI: http://dx.doi.org/10.7554/eLife.14846.004
10.7554/eLife.14846.005 Figure 1—figure supplement 2.
…”
Section: Resultscontrasting
confidence: 88%
“…This eliminates a controversy with data indicating that PKMζ may be not crucial for memory maintenance ( Lee et al, 2013 ; Volk et al, 2013 ). Additional evidence of PKMζ necessity for memory storage in invertebrates has been published recently ( Balaban et al, 2015 ) and its role in memory has been shown without inhibitors, using the effect of PKMζ overexpression in the hippocampus on behavior and LTP in rats ( Schuette et al, 2016 ).…”
Section: Introductionmentioning
confidence: 97%
“…This idea is based on the following data: Long-term potentiation and memory are accompanied by increasing of the PKMζ protein level in memory-associated structures [ 79 , 80 , 81 , 82 ]; PKMζ inhibitor ZIP erases established memory in mammals and invertebrates [ 73 , 74 , 75 , 82 , 83 ]; PKMζ inhibitor ZIP disrupts the late phase of long-term potentiation, a cellular model of synaptic plasticity and memory [ 72 , 81 , 84 ]; Knockdown of PKMζ in the hippocampus impairs long-term potentiation and negatively regulates memory maintenance [ 85 , 86 ]; Overexpression of PKMζ enhances memory [ 87 , 88 , 89 ]. …”
Section: Protein Kinase Mζ Its Functions and Regulation Of Its Trmentioning
confidence: 99%